Practices and Processes in BIM Projects: An Exploratory Case Study - Conrad Boton; Daniel Forgues (Advances in Civil Engineering)
The results of an exploratory case study dedicated to a BIM project are presented and the perception that professionals have of their practices and the BIM collaboration processes is discussed in this study. It suggests that the roles of BIM specialists are not the same from one discipline to another and that they are not just technical roles. In addition, the information subprocess seems to crystallize around BIM managers, which tends to create two sources of leadership in a project: BIM managers and project managers. Finally, the study shows a gap between the planned processes and those actually used in the project. The use of a big room, to bring together the owner and the other disciplines, seems to be particularly useful. It serves as an integrator, and information is better shared.